Fiction as a Means to Understanding the Dynamics of Empathy: A 3-year Empirical Study with Students - Fåhraeus, Anna W. E. (Educare, 2020)
The current study investigated whether the reflective reading of fiction can provide an experiential definition of empathy to supplement more traditional concept analyses. A secondary aim was to look at the rates of absorption (loss of time and space) relative to the rate of reported empathic engagement. Based on earlier studies on reading fiction as an engagement in a social simulation, it was predicted that because fiction is a controlled experience, reading and talking about fiction could provide a forum in which to examine actual experiences of empathy elicitation in relation to an evolving situation. A survey was conducted with 210 student participants over a three-year period. The results show that the empathetic response to narrative is affected in a variety of ways by the presence or absence of an initial sense of affinity and by cognitive input over time, that is, the changing perception of characters and the situations with which they are confronted. Adept readers are more likely to experience absorption, and those who experience absorption are more likely to be empathetically responsive to input and changes in a situation. Empathetic emotions and cognitive empathy can be experienced for multiple objects simultaneously in one situation and relate to past events and potential futures, but they also shift from object to object.